2020
DOI: 10.21203/rs.3.rs-102560/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety, Tolerability, Pharmacokinetics and Pharmacodynamics of Single Oral Doses of Bi 187004, an Inhibitor of 11beta-hydroxysteroid Dehydrogenase-1, in Healthy Male Volunteers With Overweight or Obesity

Abstract: BackgroundThe study characterizes safety, tolerability, pharmacokinetic and pharmacodynamic profiles of single rising doses of the 11beta-hydroxysteroid dehydrogenase-1 (11beta-HSD1) inhibitor BI 187004 in healthy men with overweight or obesity.MethodsThis was a randomized, double-blind, parallel group, placebo-controlled study with administration of 2.5-360 mg BI 187004 or placebo once daily as single dose in 72 healthy volunteers with overweight or obesity.Assessments included 11beta-HSD1 inhibition in the l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 18 publications
4
11
3
Order By: Relevance
“…In the investigated dose range of 10-360 mg, there were no hypoglycemic events, and the blood pressure, heart rate, or QTc time in the ECG were not affected. Compared to the SRD study in healthy volunteers [12], where 16.7 % in the BI 187004 group and 5.9 % in the placebo group had a drug-related AEs, the study described here showed 51.8 % drug-related (BI 187004) AEs and 35.7 % in the placebo had AEs. The earlier study treated the healthy subjects with a single dose of BI 187004, while the currently described study treated the healthy subjects over 14 days; therefore, the absolute number of AEs is substantially higher in the current study.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…In the investigated dose range of 10-360 mg, there were no hypoglycemic events, and the blood pressure, heart rate, or QTc time in the ECG were not affected. Compared to the SRD study in healthy volunteers [12], where 16.7 % in the BI 187004 group and 5.9 % in the placebo group had a drug-related AEs, the study described here showed 51.8 % drug-related (BI 187004) AEs and 35.7 % in the placebo had AEs. The earlier study treated the healthy subjects with a single dose of BI 187004, while the currently described study treated the healthy subjects over 14 days; therefore, the absolute number of AEs is substantially higher in the current study.…”
Section: Discussioncontrasting
confidence: 84%
“…It has to be taken into account that on day 15, trough tissue concentrations were measured, whereas, on day 2, non-trough tissue concentrations were measured as the AT biopsies were taken 10-45 min after the second dose for logistical reasons (▶ Table 3). In healthy male volunteers, the AT/plasma ratio of BI 187004 was in the range of 8.58-11.4 % 24 h after a single dose BI 187004 [12]. As described previously [15], in response to 11beta-HSD1 inhibition in peripheral tissues, mainly liver and AT, serum cortisol levels tend to decrease, and due to negative feedback of the HPA axis, a compensatory increase of ACTH and adrenal cortisol secretion is seen.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations